Learning Uzbek grammar using artificial intelligence - Komilova, Zulhumor; Muhammadumarova, Shakhnoza (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article provides an in-depth analysis of how to learn the grammar of our native language (uzbek) using artificial intelligence (AI) technologies. The main focus is on the role of artificial intelligence in education. It also asseses the possibilities of AI in teaching Uzbek grammar, as well as their advantages and disadvantages.